Governance of illegal, unreported, and unregulated (IUU) fishing in Bangladesh: status, challenges, and potentials - Mozumder, Mohammad Mojibul Hoque; Uddin, Mohammad Muslem; Schneider, Petra; Deb, Dibash; Hasan, Mehedi; Saif, Safwa Bente; Nur, As-Ad Ujjaman (Frontiers in Marine Science, 2023)
Illegal, unreported, and unregulated (IUU) fishing can result in loss of revenue, environmental damage, and economic loss for coastal communities, as well as a reduction in fish stocks. This study aims to generate comprehensive knowledge of the historical patterns and current status of IUU fishing in the coastal and marine waters of Bangladesh (BD). Secondary, qualitative, and quantitative data were gathered using SWOT as the conceptual framework. Cluster analysis was performed using NVivo for quantitative and qualitative data analysis. This study found that, because of the lack of appropriate and robust governmental laws, regulations, and manpower, IUU fishing in BD has led to the extinction of important fish species, biodiversity loss, and increased poverty among fishers. Potential solutions include raising the standard of living for underprivileged fishermen, improving the management and oversight of artisanal and industrial fishing, motivating and training stakeholders, and coordinating across all stakeholder levels. This study serves as a crucial guideline for sustainably managing fisheries and developing legislation, rules, and regulations to prevent IUU fishing in BD.